A problemática da formação da identidade moderna e multicultural em Sandel e Taylor - Melo, Marcelo Rodrigues de (2019)
The central theme of this dissertation is the identity formation and the modern problematic that surrounds it. Two elements are central to this problem: the first is the thesis of identity formation independently of cultural content; the second is the political stance appropriate to the multicultural issue. Thus, the purpose of this paper is to investigate whether Taylor's and Sandel's criticisms of the liberal proposals of neutrality toward substantive conceptions of good are pertinent if their proposals to deal with the challenges of a plural society are feasible without falling into the challenges of a perfectionist state and, lastly, whether its proposals collaborate with each other. Methodologically, this dissertation is divided into two chapters, the first to deal with identity in the individual sense and the second to deal with identity in a collective sense. The first chapter is divided into two parts. The first relates to the formation of identity and the relationship between identity and morality. The second part deals with the relations of individual identity and modernity, their challenges and their evolution. The second chapter is divided into three parts: the first defines the problematic of multiculturalism; the second presents the proposals and challenges of Rawls and Kymlicka's neutral/voluntarist vision and the narrative vision of Sandel and Taylor; the third articulates and combines the different proposals to deal with multiculturalism.